Letter writing, an alternative approach in teacher education - Jónsdóttir, Guðrún; Dyrnes, Eva Martinsen (Nordic Journal of Comparative and International Education (NJCIE), 2019)
Instead of telling prospective teachers who they should be, we asked them: “Who are you?” We used a narrative approach to explore their own perspectives. The students were invited to share their thoughts and experiences in letter format. This letter-writing assignment was part of a course on intercultural school practices. We viewed the students’ narratives in light of J. P. Gee’s distinction between discourse with lowercase “d” and Discourse with a capital “D.” The students cited their families as being their most important formative factor, facilitating a safe and active childhood. Emphasis was also placed on where they grew up, with nature a mere “all-weather boot” step away, and where bicycle locks were unnecessary.